The Trajectory of Offending Risks: Implications for Rehabilitation and Practice - Tan, Aston (The prison journal, 2020)
Research has demonstrated myriad factors that contribute to one’s propensity to offend. However, similar research on the Asian, and specifically Singaporean, correctional population has been limited and extant Western research may not be culturally generalizable. This study explored the facets and trajectory of offending risks in Singaporean adult male offenders and their implications for offender rehabilitation and practice. Results suggest that offender rehabilitation should focus on interventions that maintain treatment continuity through the institutional and community phases, and that alternatives to incarceration may reduce unskilled and poorly adjusted ex-offenders in the workforce and society.